Working media women : profile, work environment, and job satisfaction - Murthy, D. V. R.; Anita, G. (New Delhi : Kanishka Publishers, Distributors, 2009)
Study with reference to three cities of Andhra Pradesh, India namely Hyderabad, Vijayawāda, and Vishakhapatnam.
Includes bibliographical references and index.
Keywords: Women in the mass media industry -- India -- Andhra Pradesh -- Case studies